Edukasi Bahaya Handphone bagi anak-anak SD Negri 70 Oku - Pratiwi, Cindy; Widodo, Sandi; Nuryadi, Syaipul; Putri, Yuliantini Eka (Penerbit Goodwood, 2025)
Purpose: This study aims to provide digital literacy education to increase students’ awareness of the negative effects of excessive mobile phone use. The activity focuses on instilling responsible and balanced digital habits among elementary school students through early education and behavioral modeling. Research methodology: The program was conducted using an educational approach that combined interactive counseling, visual media, and simulation-based learning. A total of 100 students from grades IV to VI at Public Elementary School 70 OKU participated as respondents. Pre- and post-session evaluations were used to measure changes in understanding regarding the risks of excessive mobile phone use. Results: The results showed that 80% of students demonstrated an improved understanding of the negative impacts of mobile phone use, including reduced concentration, health risks, and social isolation. Teachers and parents also showed strong engagement, supporting the cultivation of healthy digital behavior among children. Conclusions: This educational initiative successfully increased digital awareness and encouraged collaboration between schools, teachers, and parents. It proved effective as a preventive measure to reduce the risks associated with technology misuse among children. Limitations: The study was limited to one elementary school and a short evaluation period; thus, the long-term behavioral impact was not assessed. Contribution: This activity contributes to early digital literacy education by promoting healthy technology habits and highlighting the importance of joint supervision between families and schools in the digital era.